Discurso jurídico e religiosidade no Supremo Tribunal Federal: análise crítica de discurso jurídico (ACDJ) sobre a fundamentação de decisões do STF. - Abreu, Rogério Roberto Gonçalves de (2021)
The present work presents this problem: is there religious traces in the textual reasoning in decisions of the Supremo Tribunal Federal (Brazilian Supreme Court)? The research assumes that the decision-maker, given her human nature, lies exposed to the influences from her unconscious and her ideological common sense, features culturally incorporated by the inputs of a whole history of life. Thus, the hypothesis is affirmative. At the same time, the research takes into account the constitutional definition and the judicial construction of a brazilian model of laicity that establishes autonomy between political and religious fields and that assures to all the people the entitlement and exercise of religious liberties. This discipline entails, in an a priori sense, the inadmissibility of decision-making by judges to be grounded on their personal religious values and principles, lest they make their decision politically illegitimate and juridically void. All these statements seem to justify the research. The general goal is to investigate and characterize traces of religiosity in the textual reasoning of judicial decisions uttered by the brazilian Supreme Court. The first chapter characterizes the role of the fundamental right to contradictory and effective cooperation in court as a stand to the legitimation of jurisdiction, procedure and judicial decision; examines the anatomy of judicial decision, emphasising its reasoning part in its grounding and justification moments; at least, anchored on ideas about the freudian unconscious, the myth of judicial neutrality and empirical research on judicial decisions, it examines the role of meta processual factors in the judicial decision-making process, emphasizing the judges religious values. The second chapter approaches to theories of language, discourse, social fields, ideology and juridical discourse to compose its methodological apparatus grounded on Virgínia Colares’ Critical Juridical Discourse Analysis (CJDA), developed from Norman Fairclough’s model. The third chapter presents the foundations of the brazilian model of laicity as a base theory, defines criteria to build the research corpus, pointing out the decisions to be examined. After that, it applies the analytical categories and procedure referred to in chapter two on the corpus, describing the results by decision and by justice in the first moment and presenting a reflexive and critical brief to the findings in a comparative approach after that. In the end, the research confirms the hypothesis, categorizing the traces of religiosity according to analytical categories of meaning dimensions employed in CJDA. The research defines itself as qualitative, inductive, bibliographical and documental, mainly building upon to CJDA as a methodological tool. In conclusion, this work considers that the brazilian model of laicity does not close the doors of courts to the meanings mobilyzed from the religious field, yet the values sustained by the hegemonic religious denominations do not affect the results of decisions.